Enhancing fraud prevention and detection by profiling fraud offenders - Kapardis, Andreas; Krambia-Kapardis, Maria; Kapardis, Andreas (My University, 2004)
Aims: The paper first focuses on the crime of fraud and then on approaches to profiling offenders before examining closely studies of fraud offenders and their motivation. Method: Drawing on the existing empirical literature, a profile of the serious fraud offender is presented and critiqued together with a taxonomy of such offenders comprising 12 types. Conclusions: The implications of the findings for fraud detection and prevention are discussed.
Keywords: Crime; Forgery; Motivation; Personality; Crime; Forgery; Motivation; Personality